Endoscopic versus surgical treatment of ampullary adenomas: a systematic review and meta-analysis - Ernesto Quaresma Mendonça; Wanderley Marques Bernardo; Eduardo Guimarães Hourneaux de Moura; Dalton Marques Chaves; André Kondo; Leonardo Zorrón Cheng Tao Pu; Felipe Iankelevich Baracat (Clinics, 2016)
The aim of this study is to address the outcomes of endoscopic resection compared with surgery in the treatment of ampullary adenomas. A systematic review and meta-analysis were performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. For this purpose, the Medline, Embase, Cochrane, Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), Scopus and Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases were scanned. Studies included patients with ampullary adenomas and data considering endoscopic treatment compared with surgery. The entire analysis was based on a fixed-effects model. Five retrospective cohort studies were selected (466 patients). All five studies (466 patients) had complete primary resection data available and showed a difference that favored surgical treatment (risk difference [RD] = -0.24, 95% confidence interval [CI] = -0.44 to -0.04). Primary success data were identified in all five studies as well. Analysis showed that the surgical approach outperformed endoscopic treatment for this outcome (RD = -0.37, 95% CI = -0.50 to -0.24). Recurrence data were found in all studies (466 patients), with a benefit indicated for surgical treatment (RD = 0.10, 95% CI = -0.01 to 0.19). Three studies (252 patients) presented complication data, but analysis showed no difference between the approaches for this parameter (RD = -0.15, 95% CI = -0.53 to 0.23). Considering complete primary resection, primary success and recurrence outcomes, the surgical approach achieves significantly better results. Regarding complication data, this systematic review concludes that rates are not significantly different.